Determination of live and dead Komagataeibacter xylinus cells and first attempt at precise control of inoculation in nanocellulose production. Issue 2 (25th October 2019) - Zou, Xiaozhou; Zhang, Shuo; Chen, Lin; Hu, Junqing; Hong, Feng F.
Summary: The timely enumeration of cells of nanocellulose‐producing bacteria is challenging due to their unique growth properties. To better understand the metabolism of the bacteria and better control the concentration of living cells during cultivation, a prompt cell counting technology is crucial and urgently required. In this work, two fluorescent dyes, the asymmetrical anthocyanidin dye SYBR Green I (SG) and propidium iodide (PI), were first combined for Komagataeibacter xylinus species to determine live/dead bacterial cells quantitatively and promptly. The number of live and dead K. xylinus cells determined using an epifluorescence microscope corresponded well to the results obtained using a fluorescence microplate reader. The R 2 values were 0.9986 and 0.9920, respectively, and were similar to those obtained with the LIVE/DEAD ® BacLight TM commercial kit. SG/PI double‐staining showed proper efficiency in distinguishing live/dead cells for the K. xylinus strain ( R 2  = 0.9898). The technology was applied to standardize four different K. xylinus strains, and the initial cell concentration of the strains was precisely controlled (no significant difference among the strains, P >   0.05). The cellulose yield per live cell was calculated, and significant differences ( P  <   0.05) were found among the four strains in the following order: DHU‐ATCC‐1> DHU‐ZCY‐1> DHU‐ZGD‐1> ATCC 23770. The study shows (i) the application of the SG/PI staining to standardizing inocula for bacterial cellulose production so that a more accurate comparison can be made between different strains, and (ii) the lower cost of using SG rather than the SYTO 9 of the commercially available LIVE/DEAD ® BacLight TM kit. Abstract : The asymmetrical anthocyanidin dye SYBR Green I was first combined with propidium iodide to determine live/dead bacterial cells quantitatively and promptly for Komagataeibacter xylinus species. The fluorescence staining technology was applied to standardize four different K. xylinus strains in a timely fashion to give a more accurate comparison. The study is the first attempt at precise control of inoculation in bacterial nanocellulose production.